What is the significance of a new breast mass in women aged 40 or above? A cross-sectional study - Sadaf Alipour; Kasra Jafari; Azin Saberi; Mandana Motamedi; Amirhossein Eskandari (PLoS ONE, 2026)
Background Breast lumps are the most common presentation of breast cancer, and when detected in imaging, they are assigned a BI-RADS score dependent on their characteristics. Recency of a mass is not among these features, while in our center, the new occurrence of a solid breast mass in women 40 or above is considered suspicious because common benign masses typically occur before this age. We designed this study to evaluate data from our Arash Breast Diseases Registry to explore the results of this personalized approach. Methods Women aged ≥40 with a breast mass in exam, ultrasound, or mammography that had been biopsied or followed-up for at least 2 years were included. In addition to BIRADS 4 and 5 or suspicious clinical exam, new solid masses on breast examination, mammography, or ultrasound in women 40 or above were biopsied. We calculated the sensitivity, specificity, likelihood ratios, and predictive values for our institutional protocol and the guideline-based protocol where the recency of the mass is not an indication for biopsy. Results Among 4865 women, 609 were eligible. The mean age was 49.06 ± 7.84 years; 135 were malignant, and 474 were benign. Our protocol showed an increase in the sensitivity (84.1% vs. 70.1%) and a decrease in specificity (40.3% vs. 95.4%) when compared to the usual protocol. Conclusions While our institutional protocol increased the sensitivity and could lead to early detection, it lowered specificity, suggesting more false positive results. Our main suggestion is to consider “recency of a solid mass” as a criterion for suspiciousness in BI-RADS assignment to breast masses. We propose further studies to achieve a protocol that maximizes both sensitivity and specificity without compromising diagnostic reliability, and to find the cut-off for age when the effect of this factor increases.